Human Resources and Work Ethic in Sharia - Indra Sudrajat (Values: Jurnal Kajian Islam Multidisiplin, 2025)
The birth of the Islamic economic system coincided with the birth of Islam. The Islamic economic system was not born due to the failure of other current economic systems, such as capitalism, socialism, and so on. The Sharia economic system is the embodiment of the Islamic paradigm. The development of the Sharia economy and the Sharia economic system is not intended to compete with the capitalist or socialist economic systems, but rather to create an economic system with advantages that offset the shortcomings of existing economic systems. As Muslims, we are required to prioritize not only the afterlife or the worldly, but a middle ground between the two. This middle ground means not being neglected by the pursuit of wealth alone, but striving and always remaining close to Allah SWT. Neglecting those under one's responsibility means failing to provide for one's wife and children according to one's capabilities. These teachings will inspire a Muslim to strive hard in all areas of life, rather than simply resigning himself to fate.